STUDY OF INTERGRANULAR CORROSION ON NON-HEAT TREATABLE ALUMINUM ALLOYS IN A COMPRESSOR AFTER-COOLER - D.N. Adnyana (Metalurgi, 2021)
This study was carried out on a compressor heat exchanger (after-cooler) which had a leak in the welded joint of its components made of non-heat treatable aluminum alloys. The purpose of this study is to determine the type and cause, and mechanisms of failure associated with the metallurgical structure that occurs. In this study a number of tests have been carried out including visual and macroscopic examinations, metallographic and hardness testing, and SEM (scanning electron microscopy) analysis equipped with EDS (energy dispersive spectroscopy). The results of the study obtained indicate that the failure mechanism that causes leakage in the aluminum alloy welding joints of the compressor heat exchanger component is intergranular corrosion due to sensitization and the related effect of environmental factors that occur. In addition, the failure may also be affected by welding defect in the form of pinholes.